Some biochemical properties of arginase in sheep mammary tissue - Özçelik, M; Özdemir, N (Scientific Technical Research Council Turkey, 2003)
In this study, some biochemical properties of arginase in sheep mammary tissue were examined. Preincubation temperature, preincubation period and pH were determined to be 52 degreesC, 12 min and 9.7, respectively. Furthermore, it was found that arginase in sheep mammary tissue was sensitive to different metal ions. It was found that the most effective was Mn+2 from among Mn+2, cu(+2), Mg+2, Ba+2, Fe+3, Ag+2, Cr+3, Sn+2, Hg+2, Pb+2, Co+2, Ni+2, Zn+2 and Ca+2 metal ions. Arginase showed the highest activity in a 0.75 mM MnCl2 concentration. Manganese ions and preincubation were necessary for the activation of the enzyme. Sn+2, Pb+2 and Cr+2 showed no activity. The relationship with the enzyme substrata was evaluated according to Michaelis-Menten and the Km value was 1.35 mM.
Koyun meme doku arjinazinin bazi biyokimyasal özellikleri
Keywords: arginase; sheep mammary tissue; kinetic properties